Estimation of biogas co-production potential from liquid dairy manure, dissolved air flotation waste (DAF) and dry poultry manure using biochemical methane potential (BMP) assay. (May 2020) - Johannesson, Gudmundur H.; Crolla, Anna; Lauzon, John D.; Gilroyed, Brandon H.
Abstract: Optimized biogas output and operational stability of farm-based anaerobic digester (AD) systems depends on substrate availability and quality. Economic and environmental performance is enhanced by using locally available off-farm co-substrates that have the potential to improve biogas output, but may cause inhibition or toxicity in the co-digestion process. To that end, biochemical methane potential (BMP) of liquid dairy manure (LDM) with solid poultry manure (SPM) and dissolved air flotation waste (DAF) was evaluated in a 62-day assay. Specific methane yield (SMY) ranged from 236 to 398 ml CH4 ·g VS -1, with up to 25% and 161% increase in biogas output from LDM and SPM, respectively, in co-digestion compared to monosubstrates only. However, indications of inhibition or beginning toxicity that merit further study, at higher levels of LDM and DAF were likely due to inhibitors in the digestion process from high free ammonia (NH4 or NH3 ) content from SPM, or the long chain fatty acid (LCFA) content of DAF. Findings in this study suggest opportunity in value added and environmentally sound recycling of low grade off-farm waste as AD feedstock in farm ADs while maintaining operational stability. The study expands on the use of marginal waste that may be the only regionally available source of substrate.